Types of Code Switching Used in The Naked Traveler Novel - Dwinesa Anggraeni (Scope : Journal of English Language Teaching, 2021)
Human is a social creature who needs to link and to communicate with each other. The potential relationship of individuals who speak more than one language lead to a bilingual community. Speakers who have been exposed to two languages sometimes switch code within a domain or a social situation. Today it is very common for some authors to use two different languages in their master piece, in form of novels or other pop culture. Some authors recently throw their readers to the deep story by using two languages where they switch from one language to another. The purpose of this research aims to identify the types of code-switching found in The Naked Traveler Novel written by Trinity as well as to define the most dominant type of code-switching found in The Naked Traveler Novel written by Trinity. The researcher used the theory of Romaine in Susanto (2008) that is classified into three types of code-switching, there are inter-sentential code-switching, intra-sentential switching, and tag switching. The qualitative descriptive method used in collecting and analyzing the data. From the result, it is found that there are 3 inter-sentential code switching with 12%, 22 intra-sentential type of code switching with 88%, and zero found for tag switching.